2020
DOI: 10.3390/ijerph17093134
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Duty-Related Posttraumatic Stress Disorder among Police Officers in the Mt. Ontake Eruption Disaster-Support Task Force

Abstract: Mount Ontake in Nagano Prefecture, Japan erupted on 27 September 2014. Many police officers were called in for duty as a disaster-support task force. We investigated the association between the peritraumatic situation and posttraumatic stress disorder (PTSD) symptoms in these police officers. In January 2015, a health survey (OHS) on disaster stress related to the Mt. Ontake eruption disaster support work was distributed to all of the police officers and staff involved in the disaster support. We analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
1
2
0
6
Order By: Relevance
“…In our interviews, participants expressed a lack of preparation for deployment, specifically a lack of rest and poor sleep quality. These results are consistent with previous research that has shown that rescue workers' health status, inability to fully regain energy, exhausted from disaster-support work, and perceived physical disturbances play an important role in the creation of work-related stress and aggravate the psychological burdens they face [30,31]. Unpredictable situations involving a threat to human life, such as those faced by disaster rescue workers, have been shown to cause an increase in cardiac sympathetic excitation [32].…”
Section: Comparisons With the Literaturesupporting
confidence: 91%
“…In our interviews, participants expressed a lack of preparation for deployment, specifically a lack of rest and poor sleep quality. These results are consistent with previous research that has shown that rescue workers' health status, inability to fully regain energy, exhausted from disaster-support work, and perceived physical disturbances play an important role in the creation of work-related stress and aggravate the psychological burdens they face [30,31]. Unpredictable situations involving a threat to human life, such as those faced by disaster rescue workers, have been shown to cause an increase in cardiac sympathetic excitation [32].…”
Section: Comparisons With the Literaturesupporting
confidence: 91%
“…Human service practitioners such as nursing practitioners, physicians, therapists, child protection workers, police officers, and first responders often respond to potentially traumatic events or incidents and are requested to help traumatized individuals as part of their duties (Cluster #0, Cluster #5, Cluster #6, Cluster #7, and Cluster #10) ( Musa and Hamid, 2008 ; Blau et al, 2012 ; Jacobson, 2012 ; Giada et al, 2017 ; Denkinger et al, 2018 ; Greinacher et al, 2019a ; Kamijo et al, 2020 ; Maran et al, 2020 ; Vagni et al, 2020b ; Smith et al, 2021 ). Recently, researchers have found that an individual may show positive changes following a traumatic event, such as treasuring life more, enhancement of close relationships, recognizing and elaborating on personal strengths, recognizing new possibilities, and spiritual development ( Tedeschi and Calhoun, 1996 ; Tedeschi and Calhoun, 2004 ; Ogińska-Bulik and Kobylarczyk, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of the development of PTSD is higher among women (Creamer et al 2001;Kamijo et al 2020;Syed et al 2020), young people (at the age of 15-24) (Bromet et al 1998), those who are married (Creamer et al 2001), those who have longer time in policing (Dudek 2003;Syed et al 2020;Wagner et al 2020), and those who have problems with talking about their emotions or experience emotional exhaustion (Carlier et al 1997;Meffert et al 2008;Wagner et al 2020). The factors that accelerate the development of PTSD are experiencing shame and anger as a response to other people's reaction to one's participation in a traumatic event (Dudek 2003;Papazoglu et al 2020), a number of traumatic experiences in the young age (Buchanan et al 2001), the intensity of the experienced trauma, multiple participation in traumatic events, and a lack of support/insufficient support (Carlier et al 1997;Ma et al 2015;Marmar et al 2006;Mona et al 2019;Violanti et al 2018;Wagner et al 2020).…”
Section: Risk Factors For the Development Of Ptsdmentioning
confidence: 99%